Chitosan as an antioxidant alternative to sulphites in oenology: EPR investigation of inhibitory mechanisms. (1st July 2019) - Castro Marín, Antonio; Culcasi, Marcel; Cassien, Mathieu; Stocker, Pierre; Thétiot-Laurent, Sophie; Robillard, Bertrand; Chinnici, Fabio; Pietri, Sylvia
Highlights: Metal chelation and free radical scavenging in wine oxidation were tested by EPR. A dose of 2 g/L of approved chitosan efficiently stabilized an unsulphited white wine. Inhibition of Fe(II)/Fenton chemistry and scavenging of hydroxyl radicals are involved. Concomitant decreased acetaldehyde formation was observed. Abstract: The efficacy against oxidative degradation in model and sulphite-free white wines of two commercial, insoluble chitosans (one being approved for winemaking) were investigated by electron paramagnetic resonance (EPR). Both compounds at various doses significantly inhibited the formation of α-(4-pyridyl-1-oxide)- N - t -butylnitrone (4-POBN)-1-hydroxyethyl adducts under normal wine storage conditions. Pre-incubation with 2 g/L chitosan followed by filtration had a better effect than adding 50 mg/L sulphur dioxide to the experimental Chardonnay wine on the release of 4-POBN adducts after 6 days of incubation with 100 μM iron(II). In a relevant photooxidative system acetaldehyde formation was significantly reduced after 6 days of incubation. Parallel EPR tests were performed to assess the importance of metal chelation (iron and copper) versus direct scavenging of hydroxyl radicals on the effect of chitosan. The present data support the potentiality of using biocompatible chitosan as a healthier complement and/or alternative to sulphur dioxide against white wine oxidative spoilage.